Pengaruh Experience Marketing, Nilai Pelanggan Dan Kepuasan Konsumen Terhadap Loyalitas Pelanggan Go-Jek Di Surakarta - Pamungkas, Caesar Fiero (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2019)
The research aims to find out and describe the influence of either simultaneously or partialexperiential marketing, customer value, consumer satisfaction on GO-JEK customer loyalty inSurakarta.This research using quantitative descriptive research design. The population is allconsumers who use GO-JEK services in Surakarta infinity people. The number of samples wasdetermined by the formula Hair et al and the results were 100 respondents. The sampling techniqueusing a purposive sampling method. The questionnaire is used for data retrieval. Data analysistechnique used was statistic analysis.The results showed that the experiential marketing F test,customer value, customer satisfaction simultaneously and significantly influenced the GO-JEKcustomer loyalty in Surakarta. The results of the t test show that experiential marketing has a positiveand significant effect on GO-JEK customer loyalty in Surakarta. Customer value does not have apositive and significant effect on GO-JEK customer loyalty in Surakarta. Consumer satisfaction has apositive and significant effect on GO-JEK customer loyalty in Surakarta. The regression model in thisstudy is Y = 9,407 + 0,251X_ (1) + (-0,081X_2) + 0,434X_3 + e. The results of the determination ofthe coefficientindicates experiential marketing, customer value, and consumer satisfaction have aninfluence of 19.4%. towards GO-JEK customer loyalty in SurakartaKeyword: Customer Loyalty, Experiental Marketing, Customer Value, Consumer Satisfation